(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper conducts a systematic review of oil and gas industry contracts, focusing on agreements between holders of mineral rights and exploration and production companies. The research is carried out in two stages. The first stage involves a comprehensive document review of 31 items, including legal documents, reports, and white papers related to oil and gas contracts. These documents, sourced from legal databases, publishers, and Google Scholar, primarily address petroleum production in the United States, with some covering international oil contracts and landowners’ agreements with wind energy developers. The review assesses the sophistication of modern contracts, the legal language used, and the structure of contract clauses. This foundational work informs the content analysis of industry-standard contracts, which will be the focus of the second stage of the project. The study highlights the complexity of legal language in oil and gas contracts and its implications for inexperienced translators and legal professionals. The paper aims to bridge the gap in the literature by providing a comprehensive view of the terms and conditions in extractive contracts, offering insights into common terminological issues and clause composition.